(NmAGNETOHIMIQ (B:s (NpER(B. (NS ANGL(B. /s - (NkARLIN(B, (NrI^ARD lX@ISs; (NsOBOLEW(B, (Ns(B.(Ns(B.s; (NlAPU[KIN(B, (Ng(B.(Ni(B.s; (NzELENCOW(B, (Nw(B.(Nw(B.s ((NmOSKWA (B:s (NmIR(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 370-393s
(NpREDM(B. (NUKAZ(B.: (NS(B. 394-396s
Keywords: (NmAGNETOHIMIQs